CAMPYLOBACTERIOSIS ANALYSIS FOR JOHNSON COUNTY, KANSAS - Megee, Rebecca (My University, 2016)
Johnson County is the most populated county in Kansas, with 575,000 residents. Campylobacteriosis is one of the most common enteric diseases reported in Johnson County. Its occurrence is reportable by law to the Kansas Department of Health and Environment. The purpose of this Campylobacteriosis Analysis is to look further into the burden of campylobacteriosis in Johnson County as well as compare current testing methods. The two most common testing methods for campylobacteriosis are stool culture and the stool antigen test. The stool antigen test can provide same day results but it has a variable positive predicted value ranging from 36.6% to 75.9% (Fitzgerald et al., 2016). Five hospitals in Johnson County were assessed, and it was found that the stool antigen test was the most common test in use to diagnose campylobacteriosis. Two out of the five hospitals assessed also have a protocol in place to perform stool culture confirmations on the samples, which tested positive by the stool antigen test. The culture confirmations are not required to be reported to the Johnson County Department of Health and Environment. If stool culture results were reported after the respective positive stool antigen tests, then Johnson County might see a change in the apparent prevalence of this disease. If the Johnson County Department of Health and Environment were to follow up with the hospitals’ labs to obtain the results of the culture, or the hospitals began reporting the culture results to the Health Department, then apparent campylobacteriosis numbers might decrease. Johnson County can then have a more accurate representation of campylobacteriosis cases.
Keywords: Campylobacteriosis; Johnson County Kansas